2018
DOI: 10.1093/botlinnean/box091
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of Orinus (Poaceae), a dominant grass genus on the Qinghai-Tibet Plateau

Abstract: To better understand the responses of arid-adapted, alpine plants to Quaternary climatic oscillations, we investigated the genetic variation and phylogeographic history of Orinus, an endemic genus of Poaceae comprising three species from the dry grasslands of the Qinghai-Tibet Plateau (QTP) in China. We measured the genetic variation of 476 individuals from 88 populations using three maternally inherited plastid DNA markers (matK, rbcL and psbA-trnH), the biparentally inherited nuclear ribosomal internal trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 140 publications
(204 reference statements)
2
25
0
Order By: Relevance
“…In the present, the QTP exhibits substantial landscape heterogeneity; for example, its elevation range is from 3,000 to 5,000 m and represents a steep ecological gradient comprising diverse niches for a rich composition of species (Feng et al, ; Feng et al, ; Liu, Luo, Li, & Gao, ). With respect to environmental change, the QTP has undergone extreme ecological disturbances on an evolutionary timescale, especially rapid uplifts since the Miocene–Pliocene or Miocene–Quaternary epochs and subsequent climatic oscillations in the Quaternary (Liu, ; Liu, Gao, Chen, & Lu, ; Liu, Wang, Geng, et al, ; Liu, Wang, Wang, Hideaki, & Abbott, ; Liu et al, , ; Shi, ; Shi, Li, & Li, ; Wen, Zhang, Nie, Zhong, & Sun, ; Zheng & Nat, ). The biodiversity within the QTP is reflected within its flora, which harbors ca.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the present, the QTP exhibits substantial landscape heterogeneity; for example, its elevation range is from 3,000 to 5,000 m and represents a steep ecological gradient comprising diverse niches for a rich composition of species (Feng et al, ; Feng et al, ; Liu, Luo, Li, & Gao, ). With respect to environmental change, the QTP has undergone extreme ecological disturbances on an evolutionary timescale, especially rapid uplifts since the Miocene–Pliocene or Miocene–Quaternary epochs and subsequent climatic oscillations in the Quaternary (Liu, ; Liu, Gao, Chen, & Lu, ; Liu, Wang, Geng, et al, ; Liu, Wang, Wang, Hideaki, & Abbott, ; Liu et al, , ; Shi, ; Shi, Li, & Li, ; Wen, Zhang, Nie, Zhong, & Sun, ; Zheng & Nat, ). The biodiversity within the QTP is reflected within its flora, which harbors ca.…”
Section: Introductionmentioning
confidence: 99%
“…Within the alpine grasslands of the QTP, the dominant vascular plants are three endemic species comprising the entirety of the genus, Orinus Hitchcock (Figure ; Poaceae; Liu et al, ; Su, Wu, Li, & Liu, ). Orinus consists of clonal grasses and was established in 1933 by Hitchcock based on the type species O .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Climatic oscillations and related changes in vegetation can be recognized in the period from 3.6 to 0.8 Ma (Naidina & Richards, ). Multiple studies have showed that the climate oscillations especially in the glaciation cycles of the Quaternary may have facilitated speciation, diversification, hybridization, and changes in the distribution of the global vegetation (Liu et al., ; Shahzad, Jia, Chen, Zeb, & Li, ; Yamamoto, Ohtani, Kurata, & Setoguchi, ).…”
Section: Introductionmentioning
confidence: 99%